2021
DOI: 10.32604/ijmhp.2021.016339
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mind-Body Exercise on Burnout and Stress in Female Undergraduate Students

Abstract: This study was to investigate the effects of mind-body exercise on burnout and perceived stress among female undergraduate students. A sample of 146 female undergraduate students took part in this study. They were assigned to mind-body exercise group (n = 91) and control group (n = 55). Mind-body exercise group received three 90-min sessions of Baduanjin exercise per week lasting for 12-weeks. There was no intervention in the control group. The Maslach Burnout Inventory-Student Survey was used to assess burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This can lead to the confusion and anxiety among students where it can affect their studies. Burnout has become a significant psychological issue among undergraduate students, implying that burnout might have an impact on academic performance (Zhu et al, 2021). Next is emotional and spiritual management from students themselves, which due to tiredness, stress, and the burden of online assignments and activities during learning.…”
Section: Resultsmentioning
confidence: 99%
“…This can lead to the confusion and anxiety among students where it can affect their studies. Burnout has become a significant psychological issue among undergraduate students, implying that burnout might have an impact on academic performance (Zhu et al, 2021). Next is emotional and spiritual management from students themselves, which due to tiredness, stress, and the burden of online assignments and activities during learning.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that university students' stress levels and psychological wellbeing could be improved through Baduanjin exercise. As Baduanjin exercise allows participants to practice body, breath, and mind control ( 46 )through slow, continuous movements and steady postures, which highly demand mental focus and breathing control ( 47 ). Another rationale might lie in the distraction hypothesis ( 48 )because the Baduanjin exercise is intended to induce practitioners to focus on the moment and forget about moments of stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…This method includes diverse therapeutic approaches, such as meditation, yoga, relaxation and breathing techniques, biofeedback, qigong, and autogenic training (Fogaça et al, 2021). Many researchers have applied mind-body programs to promote student mental health and have shown promising results (Cozzolino et al, 2020;Novak et al, 2020;Zhu et al, 2021). A meta-analysis by Chen et al (2021) found Erickson, 1987;Henderson, 2019;Kang et al, 2009;Kim, 2014;Meng & Qi, 2018;Song, & Lindquist, 2015;Tung, 2021).…”
Section: Other Biomedical Markersmentioning
confidence: 99%